Penentuan Daerah Rawan Kebakaran dengan Sistem Informasi Geografik (Kasus Pooncarie Region, New South Wales, Australia) - Rochmad Muryamto (Faculty of Engineering, Universitas Gadjah Mada, 2004)
The research was done to produce o map showing areas of a high bushfire risk and to create a statistic table shov'ing,.for each properfy, the totsl area with a high bushfire risk and proportion ofthe high bushfire risk area lo the total area ofthe property.The research was carried out in Pooncarie region, south western New South Wales Australia, which is best described as an area of semiarid rangeland. GIS (Geographic Information Systems) spatiul analysis was conducted usingfour coverages: Iand system, roads, bores, and property, including their coruesponding attribute data. Bffiring technique and overlay operations for spatial analysis were done using Arcllnfo GIS sofrware based on some determined criteria, yielding a map showing areas of a high bushfire risk. Five properties had the highest proportion of their land being identified as with a high bushfire risk. Keywords: bushfire, geographic information ststenn, buffering, spatia analysis.